2018
DOI: 10.1017/s0021859618000989
|View full text |Cite
|
Sign up to set email alerts
|

In vitroscreening of temperate climate forages from a variety of woody plants for their potential to mitigate ruminal methane and ammonia formation

Abstract: Feeding phenol-containing plants to ruminants has the potential to mitigate both methane and ammonia formation. In the present study, mostly woody plants, such as the leaves of trees and shrubs, were tested for their influence on in vitro fermentation. The plants selected grow naturally under temperate climatic conditions, are usually available in bulk and do not directly compete with human food production. The detailed screening included whole plants or parts of different plant species reporting their effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
1
10
0
2
Order By: Relevance
“…Supplements with low tannin levels provided the most net gas, whereas additions with higher tannin levels produced the lowest. Getachew et al [32] and Terranova et al [33] demonstrated strong connections between CT and gas production, and their findings are consistent with ours. According to Cherdthong et al [13], a positive correlation between gas production and high-CT pellet supplementation could be due to microbial activity stimulation caused by increased adverse microbiological conditions.…”
Section: In Vitro Gas Production Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…Supplements with low tannin levels provided the most net gas, whereas additions with higher tannin levels produced the lowest. Getachew et al [32] and Terranova et al [33] demonstrated strong connections between CT and gas production, and their findings are consistent with ours. According to Cherdthong et al [13], a positive correlation between gas production and high-CT pellet supplementation could be due to microbial activity stimulation caused by increased adverse microbiological conditions.…”
Section: In Vitro Gas Production Parameterssupporting
confidence: 91%
“…This finding was enhanced in part by the fact that high-CT plant materials supplementation resulted in significantly lower VFA concentrations. However, high CT and TP contents in plant materials in the substrate may have a negative effect on rumen microbial activity, decreasing gas kinetics and production [33,35].…”
Section: In Vitro Gas Production Parametersmentioning
confidence: 99%
“…Several screenings of herbal species for their nutrient and phenolic contents have been made. Examples are the studies by Macheboeuf et al (2014), who analysed a large collection of wild plants grown in the French Massif Central Area, Jayanegara et al (2011), who investigated several alpine forages, and Terranova et al (2018), who screened woody plants grown in temperate climatic conditions. Still, data on temperate-climate meadow herbs and herbaceous legumes are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous research has focused on condensed tannins (Beauchemin et al, 2008). However, vine leaves (Vitis vinifera) contain more hydrolyzable tannins than condensed tannins (Terranova et al, 2018(Terranova et al, , 2020. In vitro, vine leaves proved to be among the most efficient temperate climate shrub leaves in reducing CH 4 (Terranova et al, 2018(Terranova et al, , 2020 and they were palatable to dairy cows despite their significant tannin content (Terranova et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, vine leaves (Vitis vinifera) contain more hydrolyzable tannins than condensed tannins (Terranova et al, 2018(Terranova et al, , 2020. In vitro, vine leaves proved to be among the most efficient temperate climate shrub leaves in reducing CH 4 (Terranova et al, 2018(Terranova et al, , 2020 and they were palatable to dairy cows despite their significant tannin content (Terranova et al, 2020). Other grape vine components, including the residues from pressed grapes, have demonstrated significant antimethanogenic properties in ruminants (Moate et al, 2014).…”
Section: Introductionmentioning
confidence: 99%